2017
DOI: 10.1039/c7ra04716a
|View full text |Cite|
|
Sign up to set email alerts
|

Aqueous extract of Cordyceps sinensis potentiates the antitumor effect of DDP and attenuates therapy-associated toxicity in non-small cell lung cancer via IκBα/NFκB and AKT/MMP2/MMP9 pathways

Abstract: Cordyceps sinensisis reported as an invigorant with pleiotropic biological effects that has potential for tumor therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 41 publications
0
4
0
1
Order By: Relevance
“…The contents of four nucleosides in FCP were determined by HPLC to control the quality of FCP. The results showed that the composition of uridine, inosine, guanosine, and adenosine in FCP used in this experiment was 0.0833%, 0.0014%, 0.1148%, and 0.1025% (Cai et al, 2018; Huo et al, 2017). We found that the adenosine content in the FCP we used was much higher than the 0.010% stipulated in the 2020 edition of the Chinese Pharmacopoeia (Figure 1 and Table 1).…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…The contents of four nucleosides in FCP were determined by HPLC to control the quality of FCP. The results showed that the composition of uridine, inosine, guanosine, and adenosine in FCP used in this experiment was 0.0833%, 0.0014%, 0.1148%, and 0.1025% (Cai et al, 2018; Huo et al, 2017). We found that the adenosine content in the FCP we used was much higher than the 0.010% stipulated in the 2020 edition of the Chinese Pharmacopoeia (Figure 1 and Table 1).…”
Section: Resultsmentioning
confidence: 67%
“…Nucleosides are commonly used as quality control indicators for FCP (Huo et al, 2017). The contents of four nucleosides in FCP were determined by HPLC to control the quality of FCP.…”
Section: Identification Of Nucleoside Components Of Fcpmentioning
confidence: 99%
“…In, the study also investigated the effects of the species on the development of the H-1299 lung carcinoma cell line, and the results showed that H. erinaceus inhibited the development of this cell line by 72%, P. ostreatus by 61% and G. lucidum by 24% (Sharif et al, 2018). Huo et al (2017) used 12 different cancer cell lines (SK-MEL-28, CoLo205, Raji , HCT-116, Lewis, Hep3B2.1-7,MDAMB-453, K562, HeLa, B16F10, NCI-H460 and A549) to investigate the dose-dependent anticancer effects of two polysaccharides (AECS1 and AECS2) derived from water extracts of the Cordyceps sinensis (AECS) type fungus. As a result of the study, they reported that IC50 values of AECS1 ranged between 0.02-3.2 mg/mL and AECS2 ranged between 0.31-4.08 mg/mL.…”
Section: Anticancer Studies Of Mushroom Extractsmentioning
confidence: 99%
“…Nakamura et al [17] found that the growth of mouse Lewis lung cancer cells and B16-BL6 melanoma cells was significantly inhibited because of the adenine nucleoside A3 receptor in tumor cells stimulated by the cordycepin. Huo et al [18] found that cordycepin significantly inhibited the growth of human cervical cancer HeLa cells, human nasopharyngeal carcinoma KB cells and Ehrlich ascites tumor. The survival time of mice inoculated with Ehrlich ascites tumor was only 19 days, while that of mice treated with cordycepin can be extended to 60 days.…”
Section: Fig1 Two Dimensional Structure and Three Dimensional Conformentioning
confidence: 99%